2019
DOI: 10.1080/13543784.2019.1599859
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of the functionally selective glucocorticoid receptor agonist BI 653048 in healthy male subjects

Abstract: Parameters evaluated for the SRD study included: maximum observed concentration (Cmax); time to achieve Cmax (tmax); area under the concentration-time (AUCt) curve dosing interval (τ) from 0 extrapolated to infinity (AUC0-∞); AUCt from 0 to last quantifiable data point (AUC0-tz), and over dosing interval τ (AUCt1-t2); percentage of AUCtz-∞obtained from extrapolation (%AUCtz-∞); terminal elimination constant (λz) and half-life (t1/2); mean residence time after peroral administration (MRTpo); apparent clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Trifluoromethyl carbinol-derived compounds are an extremely well-profiled nonsteroidal class of GRLs. In the study of Harcken et al (214), a compound named BI653048 was identified. BI653048 is in the SERGA class, which binds with high affinity to the human GR.…”
Section: Bimentioning
confidence: 99%
See 1 more Smart Citation
“…Trifluoromethyl carbinol-derived compounds are an extremely well-profiled nonsteroidal class of GRLs. In the study of Harcken et al (214), a compound named BI653048 was identified. BI653048 is in the SERGA class, which binds with high affinity to the human GR.…”
Section: Bimentioning
confidence: 99%
“…BI653048 is in the SERGA class, which binds with high affinity to the human GR. They revealed that treatment with 200 mg of BI653048 can be associated with a decreased expression of FKBP5 (214).…”
Section: Bimentioning
confidence: 99%
“…After two decades with intensive programs in big pharma, only few selective ligands are in clinical trials [77], but rarely used in the clinics. Partially, this might be due to the narrow therapeutic windows of these compounds, but also because the regulation of inflammation by steroids is far more complex than just suppression of cytokines and other pro-inflammatory mediators [78][79][80].…”
Section: Accepted Articlementioning
confidence: 99%
“…However, prednisolone does reduce bone mineral density in dogs and decreases bone formation markers in humans after 1 day ( 71 , 72 ). Indeed, in a phase I clinical trial, BI653048, and prednisolone both caused decreased serum osteocalcin levels ( 26 ). Studies with other SEGRMs also concluded that osteocalcin levels in cellulo do not always reflect in vivo decreases in bone density ( 18 , 26 , 27 , 37 , 38 ), casting doubts on the value of osteocalcin as proxy for the in vivo reduction of bone mineral density.…”
Section: Bottlenecks and Pitfalls Observed In The Pastmentioning
confidence: 99%